Analisis Determinan Gross Capital Formation dan Populasi Digital Terhadap Tingkat Pengangguran Terbuka: Studi Kasus Indonesia Tahun 1994-2023 - Ayu Nathasya Nathasya; Febri Maulana Maulana; Muhammad Kahfi Putra Hazmul Hazmul; Ulfa Laviatul Nikmah Nikmah; Sugeng Hadi Utomo Utomo; Agung Nugroho Nugroho (At-Taradhi Jurnal Studi Ekonomi, 2025)
Unemployment remains a challenge for the Indonesian economy amid economic restructuring and technological developments. Investment movements and digitalization are expected to have a significant impact on labor absorption. This study analyzes the relationship between Gross Capital Formation and the internet user population on the unemployment rate in Indonesia for the period 1994–2023, and compares it with South Korea. The methods used include stationarity tests, Johansen cointegration, and multiple linear regression. The results show that Gross Capital Formation and the internet user population have a negative and significant effect on unemployment, meaning that increased investment and digitalization can reduce unemployment rates. A comparison with South Korea shows lower and more stable unemployment rates due to high investment support, equitable digital infrastructure, and competitive human resource quality. These findings emphasize the importance of strengthening productive investment and accelerating digital transformation in long-term unemployment reduction strategies